2021
DOI: 10.1089/neur.2021.0048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acute Glial Fibrillary Acidic Protein and Ubiquitin C-Terminal Hydrolase-L1 Plasma Levels in Traumatic Brain Injury Patients with and without Intracranial Lesions

Abstract: This pilot study aimed to evaluate the association of plasma ubiquitin C-terminal hydrolase-L1 (UCH-L1), glial fibrillary acidic protein (GFAP), and S100 calcium-binding protein B (S100B) with intracranial abnormalities visible on a computed tomography (CT) scan (CT positive) and injury severity in acute traumatic brain injury (TBI). For these purposes, a cohort of 109 adult TBI patients was recruited within 6 h from the injury event. A hyperacute subcohort of 20 patients who had their blood collected within 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The area under the curve (AUC) was calculated from the ROC curves to assess the performance of early UCH-L1 levels in distinguishing TBI from control patients. Early UCH-L1 levels were able to distinguish TBI from uninjured control participants with an AUC 0.87 (95% CI 0.82–0.92), indicating good predictive accuracy [ 70 , 71 ]. The area under the curve for discriminating between positive and negative intracranial lesions on CT scan was 0.73 (95% CI 0.62–0.83) [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The area under the curve (AUC) was calculated from the ROC curves to assess the performance of early UCH-L1 levels in distinguishing TBI from control patients. Early UCH-L1 levels were able to distinguish TBI from uninjured control participants with an AUC 0.87 (95% CI 0.82–0.92), indicating good predictive accuracy [ 70 , 71 ]. The area under the curve for discriminating between positive and negative intracranial lesions on CT scan was 0.73 (95% CI 0.62–0.83) [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in its concentration in the blood has been found in patients after mild traumatic brain injury (TBI). 23,24 Recent studies have also shown that GFAP concentrations in the plasma are higher in patients with AD than in controls and are also associated with amyloid pathology. [25][26][27] High concentrations of plasma GFAP have also been reported in patients with frontotemporal lobar degeneration (FTLD)-related syndromes but to a lesser extent than those in patients with AD.…”
Section: Gfap and Uch-l1mentioning
confidence: 99%
“…The intended use is for ruling out evidence of intracranial trauma on head CT. A pivotal multisite study of 1,176 individuals with acute mild TBI referenced in the US FDA documentation found this Abbott TBI diagnostic to have 99.3% negative predictive value for ruling out intracranial trauma. 23 Abbott is now developing its high throughput core laboratory ARCHITECT platform to run this assay and is also developing the i-STAT Alinity to function as a point-of-care test. GFAP can also be measured in the plasma using a commercially available Simoa-based assay.…”
Section: Blood-based Biomarker Assays Of Relevant Pathophysiologic Pr...mentioning
confidence: 99%
“…The maximum serum concentration of S100B is reached 20 min after brain damage. The normal upper limit for this protein in relation to the detection of intracranial damage was defined as 0.1 μg/l based on a multicenter study in patients with mild TBI [122]. The measurement of S100B-protein can be influenced by patient age and gender in CSF samples but not in serum samples thus making it a practically feasible biomarker.…”
Section: S100-calcium Binding Protein B (S100b)mentioning
confidence: 99%